Pengaruh Model Pembelajaran Kooperatif Tipe Trade a Problem Terhadap Minat dan Hasil Belajar Matematika - Surya; Arifin, Sartika; Muliana M, Ana (Griya Journal of Mathematics Education and Application, 2023)
Abstract This research aims to determine students' interest and learning outcomes in mathematics before and after using the trade a problem type cooperative learning model. This type of research is Pre-Experimental Design in the form of One Group Pretest-Posttest Design. The results showed that before being treated the average score of the pretest interest in learning was in the sufficient category while the pretest learning outcomes were in the very low category, and after being given treatment the average score of the posttest interest in learning was in the very high category while the posttest learning outcomes were in the high category. Students' interest and learning outcomes in mathematics after being taught using the trade a problem type cooperative learning model were higher than students' interest and mathematics learning outcomes before being taught using the trade a problem type cooperative learning model. Keywords: trade a problem learning model, interest in learning, mathematics learning outcomes Abstrak Penelitian ini bertujuan untuk mengetahui minat dan hasil belajar matematika siswa sebelum dan setelah digunakan model pembelajaran kooperatif tipe trade a problem. Jenis penelitian ini adalah Pre-Experimental Design berbentuk One Group Pretest-Posttest Design. Hasil penelitian menunjukkan bahwa sebelum diberi perlakuan nilai rata-rata dari pretest minat belajar berada pada kategori cukup sedangkan pretest hasil belajar berada pada kategori sangat rendah, dan setelah diberi perlakuan nilai rata-rata posttest minat belajar berada pada kategori sangat tinggi sedangkan posttest hasil belajar berada pada kategori tinggi. Minat dan hasil belajar matematika siswa setelah diajar menggunakan model pembelajaran kooperatif tipe trade a problem lebih tinggi dibandingkan minat dan hasil belajar matematika siswa sebelum diajar menggunkan model pembelajaran kooperatif tipe trade a problem.Kata Kunci: model pembelajaran trade a problem, minat belajar, hasil belajar matematika